Ethical behaviour of firms and corruption – a cluster analysis - Castro, Conceição; Lopes, Cristina; Ferreira, Fernanda A. (Conferência - Investigação e Intervenção em Recursos Humanos, 2019)
Corporate ethics and low corruption in the public sector are crucial to business development in an increasingly global world. Business organisations cannot disregard business ethics in order to increase performance in a society where clients are more demanding of the reputation and transparency of organisations. But business ethical behaviour is also very related with the political structures. Countries with better governance, where authority is exercised for the common good, the agents have confidence and respect the rules of the society, the government implement sound policies and regulations that allows the development of the private sector, that have high levels of public services' quality, that are politically stable, promote political, civil and human rights, and are less corrupt create a sound business environment propitiator of higher standards of corporate ethics. When the public sector is corrupt there is little incentive to maintain high standards of business ethics. In this context the purpose of this paper is to analyse the ethical behaviour of firms and corruption in the public sector, to group countries according to these indicators and to investigate the characteristics of these clusters.